2023
DOI: 10.3390/ijms24076308
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Applications of Fluorescent Perylenediimide and Perylenemonoimide Dyes in Bioimaging, Photothermal and Photodynamic Therapy

Abstract: The emblematic perylenediimide (PDI) motif which was initially used as a simple dye has undergone incredible development in recent decades. The increasing power of synthetic organic chemistry has allowed it to decorate PDIs to achieve highly functional dyes. As these PDI derivatives combine thermal, chemical and photostability, with an additional high absorption coefficient and near-unity fluorescence quantum yield, they have been widely studied for applications in materials science, particularly in photovolta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 157 publications
0
11
0
Order By: Relevance
“…We also noticed the superior fluorescence properties of perylene derivatives. 41–43 In addition, we found that DMF is an excellent plasticizer. 44 PVA organogels could be prepared when the mixed solution of PVA/DMSO/DMF was placed at room temperature for 2 h instead of photo-induced polymerization or freezing/thawing, which provides a novel strategy for the rapid preparation of organogels.…”
Section: Introductionmentioning
confidence: 76%
“…We also noticed the superior fluorescence properties of perylene derivatives. 41–43 In addition, we found that DMF is an excellent plasticizer. 44 PVA organogels could be prepared when the mixed solution of PVA/DMSO/DMF was placed at room temperature for 2 h instead of photo-induced polymerization or freezing/thawing, which provides a novel strategy for the rapid preparation of organogels.…”
Section: Introductionmentioning
confidence: 76%
“…Regarding the evaluation of greenness, all existing procedures proved underperforming from the point of view of sustainability as evaluated by their E-factors and associated hazards (2). In this respect, routes B (4300), D (4100), and E (3880) are mostly plagued by the presence of chromatographic purification steps that require ample amounts of silica and chlorinated solvents.…”
Section: Individual Step Assessmentmentioning
confidence: 99%
“…The post-functionalization can be achieved also by various surface-initiated strategies, such as "grafting to" and "grafting through" routes. [32][33][34] Perylenediimide (PDI) dyes are a well-recognized class of functional chromophores and fluorophores [35] which have been extensively used as organic n-type semiconducting materials [36] for a wide range of applications including organic solar cells, [37,38] photodynamic [39] and photothermal therapy, [40] organic lightemitting diodes and organic field effect transistors. [41] PDI based dyes have also been employed to design artificial photosynthetic systems, logic gates, molecular optical switches, photosensitizers, [42] and materials for environmental and biological analysis.…”
Section: Introductionmentioning
confidence: 99%